Genetic evidence for a protective role of Omega-3 fatty acids in nummular dermatitis - Yi Chen; Zhimin Wu; Lucy Yue Lau; Boyang Li; Yipeng Pan; Alice Yang; Yuanyuan Zhang; Chao Shu; Yifei Ma; Hongyi Zhang; Wenjia Guo (Food and Agricultural Immunology)
Background: The causal relationship between Omega-3 fatty acids and nummular dermatitis remains unclear.Methods: We performed a two-sample Mendelian randomization analysis using six independent SNPs associated with circulating Omega-3 levels. Summary statistics for nummular dermatitis were obtained from the FinnGen consortium. The inverse variance weighted method was the primary analysis, complemented by MR-Egger, weighted median, and mode-based approaches. Sensitivity analyses assessed pleiotropy and heterogeneity.Results: Higher genetically predicted Omega-3 levels were significantly associated with a reduced risk of nummular dermatitis (β = −0.25, 95% CI: – 0.45 to – 0.06, P = 0.0111). The association was consistent across multiple MR methods, with no evidence of horizontal pleiotropy or significant heterogeneity.Conclusion: This study provides the first genetic evidence supporting a protective causal effect of Omega-3 fatty acids against nummular dermatitis, highlighting the potential of nutritional interventions for inflammatory skin diseases.